2017
DOI: 10.12962/j24433527.v10i2.2865
|View full text |Cite
|
Sign up to set email alerts
|

Developing Visual Novel Game With Speech-Recognition Interactivity to Enhance Students’ Mastery on English Expressions

Abstract: The teaching of English-expressions has always been done through conversation samples in form of written texts, audio recordings, and videos. In the meantime, the development of computer-aided learning technology has made autonomous language learning possible. Game, as one of computer-aided learning technology products, can serve as a medium to provide educational contents like that of language teaching and learning. Visual Novel is considered as a conversational game that is suitable to be combined with Engli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 10 publications
0
5
0
2
Order By: Relevance
“…Though the game might have quite some errors, it is a good start to take revolutionize Indonesian tales and stories into an entertaining platform with English language, which can be enjoyed by international users. In addition, it can also be a fun learning media for English as Foreign Language (EFL) learners to be exposed with English language from which they can learn (Amalo et al, 2017;Hidayat et al, 2021;Kusumawati, 2020).…”
Section: Findings and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Though the game might have quite some errors, it is a good start to take revolutionize Indonesian tales and stories into an entertaining platform with English language, which can be enjoyed by international users. In addition, it can also be a fun learning media for English as Foreign Language (EFL) learners to be exposed with English language from which they can learn (Amalo et al, 2017;Hidayat et al, 2021;Kusumawati, 2020).…”
Section: Findings and Discussionmentioning
confidence: 99%
“…Even if those games are not intended for language learning, reducing grammatical errors can help avoiding possible confusions for the players (Heryanti et al, 2017). Though previous studies have revealed the use of game as the source of target language and investigated the grammatical errors in texts (Amalo, Agusalim, & Murdaningtyas, 2017;Atashian & Al-Bahri, 2018;Hidayat et al, 2021;Kumala, Aimah, & Ifadah, 2018;Kusumawati, 2020;Qamariah, Sri Wahyuni, & Meliana, 2020), to the best of the researchers' knowledge, they rarely conducted grammatical error analysis on games, especially those made by non-native developers. Therefore, this study intended to conduct grammatical error analysis on an Indonesian-developed game, Code Atma.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Orientation Day is the name of a visual novel game that is intended to help English learners practice conversation, pronunciation, and reading aloud [14]. The game also embraces the power of speech recognition technology for the interaction.…”
Section: Orientation Daymentioning
confidence: 99%
“…Praktiknya termasuk melakukan percakapan teks dan melafalkannya secara langsung. Akibatnya, siswa bosan karena guru terus-menerus menerapkan metode ini [5]. Selain itu, siswa juga lebih suka melakukan "silent practice" dalam membaca teks percakapan sambil belajar keterampilan berbicara bahasa Inggris dan sebagian hanya menghafalnya [6], [7].…”
unclassified